2005
DOI: 10.1111/j.1467-7679.2005.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Even the ‘Rich’ are Vulnerable: Multiple Shocks and Downward Mobility in Rural Uganda

Abstract: Poverty data rarely capture processes of change, limiting our ability to understand poverty trajectories at the individual or household levels. This article uses a household survey, village‐level participatory studies and indepth life‐history interviews to examine people's poverty trajectories and to identify what drives and maintains chronic poverty. Composite shocks can propel previously non‐poor households into severe and long‐term poverty. Poverty is hard to escape, and people born into chronically poor ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In this, our work builds on methods developed in previous work by the CPRC (Davis and Baulch, 2008;Bird and Shinyekwa, 2005). It combined quantitative analysis of the Northern Uganda Baseline Survey (NUBS) with in-depth qualitative fieldwork.…”
Section: Methods: An Iterative Q-squared Approachmentioning
confidence: 98%
“…In this, our work builds on methods developed in previous work by the CPRC (Davis and Baulch, 2008;Bird and Shinyekwa, 2005). It combined quantitative analysis of the Northern Uganda Baseline Survey (NUBS) with in-depth qualitative fieldwork.…”
Section: Methods: An Iterative Q-squared Approachmentioning
confidence: 98%
“…In development studies particularly, LHs have been used to examine poverty (Kothari and Hulme 2004;Bird and Shinyekwa 2005), well-being and economic empowerment (Locke and Lloyd-Sherlock 2011), and policy development and its implications (Chimhowu and Hulme 2006;Lewis 2008). Although LHs have 'now developed into a significant, theoretically dense, and diverse sub-set of historical and social-scientific enquiry' (Godfrey and Richardson 2004:144), they are not used in mainstream CCVA research which tends to be dominated by surveys, semi-structured interviews, and risk and impact modelling and assessments (see Supplementary Material 1).…”
Section: Life History Approachesmentioning
confidence: 99%
“…Other studies have indicated that the lack of independent rights to land can make women extremely vulnerable to downward mobility on separation, divorce, or widowhood (Bird and Shinyekwa, 2005). Without access to and control over assets and, in particular, productive resources, it has been argued that women's negotiating power within the marriage is diminished.…”
Section: What Does Inheritance Do?mentioning
confidence: 99%